Faktor-faktor yang Mempengaruhi Prokrastinasi Akademik Mahasiswa: Kejenuhan Akademik, Kecanduan Media Sosial, dan Stres Akademik - Sidqi, Moch. Hasan; Nurdiansah, Iszanul Dani; Darmawan, Didit (FONDATIA, 2025)
Academic procrastination is a common issue faced by first-year university students, particularly as they undergo the transition from secondary to higher education. This study aims to analyze the partial effects of academic burnout, social media addiction, and academic stress on academic procrastination among first-year students at Universitas Sunan Giri Surabaya. The research employed a quantitative approach using a survey method, involving 42 purposively selected first-year students. Data were analyzed using multiple linear regression to identify the contribution of each independent variable to the dependent variable. The results indicate that social media addiction has a significant and most dominant influence on academic procrastination, followed by academic stress, which also shows a significant effect. Meanwhile, academic burnout does not show a significant influence. These findings emphasize that academic procrastination among first-year students is more strongly influenced by psychosocial factors related to social media use and academic pressure. The practical implications of this study highlight the need for interventions that focus on stress management and healthy social media use to reduce the tendency to delay academic tasks among new university students.